The geography of megatrends affecting European agriculture. (July 2022) - Debonne, Niels; Bürgi, Matthias; Diogo, Vasco; Helfenstein, Julian; Herzog, Felix; Levers, Christian; Mohr, Franziska; Swart, Rebecca; Verburg, Peter
Highlights: We map megatrends to gain foresight on the future of European agriculture. Mapped megatrends are climate, demography, value system, and environmental regulation. Different regions face pressures from different combinations of megatrends. Regions range from highly susceptible to systemic change to highly persistent. For sustainability transitions, megatrends inform what governance is needed. Abstract: A range of intensifying pressures is making the future of European agriculture dynamic and contested. Insights into these pressures are needed to inform debates about the future of the sector. In this study, we use a foresight approach to identify, quantify and map megatrends. Megatrends are long-term driving forces which are observable today and will likely have transformational potential in the future. By mapping these megatrends at the regional scale, we establish a geography of megatrends and detect where they coincide. Four megatrends significant for the future of European agriculture at the regional scale are assessed: Climate change, demographic change, (post-) productivism shifts, and increasingly stringent environmental regulations. The direction and intensity of these megatrends differs between regions, which drives regions into different systemic lock-ins or dynamics. In most regions, megatrends converge to destabilize the current system, forewarning impending systemic changes. While the specific megatrends contributing to this instability differ regionally, this result highlights that many regions are on a dynamic rather than stable trajectory, and the governance challenge is to steer these dynamics towards a desirable future. However, some regions are found to be highly persistent, indicating that megatrends reinforce business as usual, and change needs to be triggered through purposeful governance. In a minority of regions megatrends may drive marginalization as the current system becomes increasingly unviable. We argue that research and policies concerning agricultural sustainability transitions should be cognizant of the regional diversity of European megatrends and the pressures they create.